Pengujian Flash Point pada Sampel Biosolar B-30 dan Pengujian Total Acid Number (TAN) pada Sampel Feedstock C PT â€œXâ€ Laboratorium Fuel Terminal BBM Bandung Group-Ujung Berung - Yully Mulyani; Dian Farkhatus Solikha; Winingsih Oktaviani (Jurnal Migasian, 2022)
Flash Point is the lowest temperature of the fuel, where if the fuel is brought close to a fire, it will ignite easily. The sample used in the flash point test is biodiesel B-30, this flash point test method uses the ASTM D 93 standard by the Pensky-Martens closed cup flash point tool. Process variables that affect flash point testing are temperature, density and pressure. The results of the flash point test with the highest flash point value are sample 4 with a value of 65.0â„ƒ, while the results of the flash point test with the lowest flash point value are sample 1 with a value of 52.0. Total Acid Number (TAN) is a combination of weak and strong acids in fuel. The sample used in the Total Acid Number (TAN) test is diesel blending feedstock C, the Total Acid Number (TAN) test method uses the ASTM D 664 standard by the Automatic Potentiometric Titrator AT -710. The process variable that affects the Total Acid Number (TAN) test is the oxidation reaction. The results of the Total Acid Number (TAN) test, the lowest acid content is diesel + feedstock C 0.3% sample with a value of 0.05527 mg KOH/gr, while the highest acid content is diesel + feedstock C 0.2% sample. with a value of 0.06708 mg KOH/gr Keywords: American Standard Testing and Material (ASTM), Blending Feedstock C, Biosolar B-30, Flash Point, Total Acid Number (TAN).